The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.jhazmat.2013.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Source attributions of hazardous aromatic hydrocarbons in urban, suburban and rural areas in the Pearl River Delta (PRD) region

Abstract: h i g h l i g h t sWe measured aromatic hydrocarbons at four contrasting sites in the PRD region. Diagnostic ratios were used to imply sources of aromatic hydrocarbons. Sources of aromatic hydrocarbons were apportioned by PMF receptor model. Solvent use, vehicle exhaust and biomass burning contributed over 89% AHs. Biomass burning contributed to AHs, particularly for Benzene in the rural. t r a c tAromatic hydrocarbons (AHs) are both hazardous air pollutants and important precursors to ozone and secondary org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 79 publications
1
81
0
Order By: Relevance
“…This implies that a larger portion of China's benzene emissions are concentrated in the densely populated coastal regions and, therefore, a large proportion of the population is exposed to elevated benzene levels in the ambient air. Previous studies in urban areas of this region, such as Beijing Zhang et al, 2012a,b;Li et al, 2014) and Guangzhou (Wang et al, 2002;Barletta et al, 2008;Zhang et al, 2013), showed much higher benzene levels when compared to those reported in Europe, or in the United States. Even early in January-February 2001, benzene was found to pose potential health risks from a survey of volatile organic compounds (VOCs) in 43 Chinese cities (Barletta et al, 2005), mostly in the eastern areas.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…This implies that a larger portion of China's benzene emissions are concentrated in the densely populated coastal regions and, therefore, a large proportion of the population is exposed to elevated benzene levels in the ambient air. Previous studies in urban areas of this region, such as Beijing Zhang et al, 2012a,b;Li et al, 2014) and Guangzhou (Wang et al, 2002;Barletta et al, 2008;Zhang et al, 2013), showed much higher benzene levels when compared to those reported in Europe, or in the United States. Even early in January-February 2001, benzene was found to pose potential health risks from a survey of volatile organic compounds (VOCs) in 43 Chinese cities (Barletta et al, 2005), mostly in the eastern areas.…”
mentioning
confidence: 56%
“…The orders (i-iv) were ranked by their lifetime cancer risks. (Tang et al, 2007;Zhang et al, 2013) and Hong Kong (Guo et al, 2011). Benzene at the SY NECP site (1297 ± 491 pptv) showed significantly lower mixing ratios when compared to those observed at rural Changchun in the NECP (2949 ± 1890 pptv; Liu et al, 2000).…”
Section: Background Benzene Levelsmentioning
confidence: 84%
See 1 more Smart Citation
“…As addressed in GB 20950-2007, implementation of emission control in China's bulk gasoline terminals had been just required since May 1st 2008, January 1st 2010 and January 1st 2012, respectively, for the BeijingeTianjian region, the Pearl River Delta region and the Yangtze River Delta region, which are three major densely populated and economically developed city clusters or megacities in China. Receptor modeling based on observed data had revealed that VOCs from oil evaporation contributed 7e30% in Beijing (Yuan et al, 2009;Wang et al, 2010), 15% in Shanghai (Cai et al, 2010), 4.3e7.6% in Hong Kong (Lau et al, 2010) and 5e10% in the Pearl River Delta region (Liu et al, 2008b;Ling et al, 2011;Zhang et al, 2012bZhang et al, , 2013 to the total man-made VOC emission.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed cryogenic concentration steps are described elsewhere (Wang and Wu, 2008;Yi et al, 2007;Zhang et al, 2013). Briefly, 250 mL air inside the canister was first concentrated through a liquid-nitrogen cryogenic trap at − 160°C.…”
Section: Ambient Bvocs Sampling and Analysismentioning
confidence: 99%